PENGARUH DAYA KREATIVITAS DAN PRESTASI BELAJAR TATA KECANTIKAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA AKS-AKK YOGYAKARTA - Harwiyati, Enny (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
This study aims to analyze the influence of creativity and cosmetology learning achievement on entrepreneurial interest in AKS – AKK Yogyakarta students. This study uses a quantitative approach with a correlational survey method. The population in this study is all students of the Cosmetology study program at AKS